Refractory traumatic bronchopleural fistula: Is extracorporeal membrane oxygenation the new gold standard?. Issue 1 (5th November 2019) - Grant, April A.; Lineen, Edward B.; Klima, Alan; Vianna, Rodrigo; Loebe, Matthias; Ghodsizad, Ali
Abstract: Introduction: A refractory bronchopleural fistula leading to respiratory failure in a trauma patient is one of the most challenging pathologies to manage in one of the most challenging patient populations. Modern equipment and techniques have decreased and perhaps even eliminated the need for anticoagulation with ECMO, and it is finding an important niche in saving this patient population from refractory hypoxia. We review here our experience with three refractory traumatic bronchopleural fistulae utilizing venovenous ECMO as the primary treatment modality. Material and Methods: Retrospective chart review of three cases of refractory traumatic bronchopleural fistula treated primarily with ECMO and an ultra‐lung protective strategy. Results: The use of an ultra‐lung protective strategy with ECMO allowed sealing of all three bronchopleural fistula. Conclusions: Traumatic bronchopleural fistulae require careful thought and early utilization of lung protective strategies to facilitate healing of the injured lung.